Increased incidence of late-onset inflammatory bowel disease and microscopic colitis after a Cryptosporidium hominis outbreak. (2nd December 2022) - Boks, Marije; Lilja, Mikael; Widerström, Micael; Karling, Pontus; Lindam, Anna; Eriksson, Axel; Sjöström, Malin
Abstract: Objectives: In 2010, 27, 000 inhabitants (45% of the population) of Östersund, Sweden, contracted clinical cryptosporidiosis after drinking water contaminated with Cryptosporidium hominis . After the outbreak, local physicians perceived that the incidence of inflammatory bowel disease (IBD), including ulcerative colitis (UC), Crohn's disease (CD), and IBD-unclassified, and microscopic colitis (MC) increased. This study assessed whether this perception was correct. Materials and methods: This observational study included adult patients (≥18 years old) from the local health care region who were diagnosed with pathology-confirmed IBD or MC during 2006–2019. We collected and validated the diagnosis, date of diagnosis, age at diagnosis, and sex from the Swedish quality register SWIBREG and electronic patient records. Population data were collected from Statistics Sweden. The incidences for 2006–2010 (pre-outbreak) and 2011–2019 (post-outbreak) were evaluated by negative binomial regression analysis and presented as incidence rate ratios (IRRs). Data were analyzed for IBD, for UC and CD separately, and MC. Results: During the study period, we identified 410 patients with new onset IBD and 155 new cases of MC. Overall, we found a trend toward an increased incidence of IBD post-outbreak (IRR 1.39, confidence interval (CI) 0.99–1.94). In individuals ≥40 years old, the post-outbreak incidence significantly increased for IBD (IRR 1.69, CI 1.13–2.51) and CD (IRR 2.23, CI 1.08–4.62). Post-outbreak incidence of MC increased 6-fold in all age groups (IRR 6.43, CI 2.78–14.87). Conclusions: The incidence of late-onset IBD and MC increased after the Cryptosporidium outbreak. Cryptosporidiosis may be an environmental risk factor for IBD and MC.